Sigle-center, observational, prospective study describing same-day discharge implementation for uncomplicated elective percutaneous coronary intervention by radial approach: Study protocol - Giovanna Silveira Lacerda de Mesquita Aquino; Júlia Braga Botelho; Camila Naomi Matsuda; Marcilene Aparecida da Silva; Bruno Laurenti Janella (Hospital de Clínicas de Itajubá, 2021)
Objectives: The study's primary objective will be to evaluate the safety and describe the initial experience of implementing early discharge (on the same day) of coronary patients from the Unified Health System undergoing elective, uncomplicated, transradial percutaneous coronary intervention. The secondary objective will be to assess the impact on the direct cost per patient compared to previously known data from the classic hospital stay used (hospital overnight). Methods: Observational and prospective study of patients undergoing elective uncomplicated transradial percutaneous coronary intervention with early discharge, respecting the inclusion and exclusion criteria. Follow-up of patients will be carried out to prove the safety of the new strategy in the population of the Unified Health System and to compare the direct costs between overnight stays and discharge on the same day. This will be the first study dedicated to primarily evaluating the safety of early discharge after elective uncomplicated transradial coronary angioplasty, validating this protocol in the population of the Brazilian public health system.